A Study of Social Support among Non-Depressed and Depressed Mothers after Childbirth in Jahrom, Iran. - Jahromi, Marzieh Kargar; Mohseni, Fatemeh; Manesh, Esmail Parsayee; Pouryousef, Sajad; Poorgholami, Farzad (Bangladesh Journal of Medical Science, 2019)
The purpose of this study was to evaluate the social support provided for non-depressed women and women with postpartum depression referring to health centers in Jahrom. Method: In order to achieve the mentioned goal, three health care centers randomly selected. 60 referring women who had the required criteria were selected by convenience sampling method and were divided into two groups of postpartum depression (30) and non-depressed (30) people. For evaluation of social support, the Phillips Social Support scale was used, and Edinburgh Postpartum Depression Questionnaire was used to evaluate postpartum depression. Data were analyzed by T-test. Results: The results showed that there was a significant difference between the non-depressed and those with postpartum depression in terms of social support (P = 0.03). These findings are remarkable in that they can be used to prevent the progression of treatment for postpartum depression. Conclusion: It is necessary to implement social and behavioral interventions in order to encourage and educate families, friends and kinship networks in order to provide socially desirable support for mothers, as well as cultural interventions in order to modify the morbidity of men to reduce postpartum depression. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.736-740